Alkaline Ceramidase Mediates the Oxidative Stress Response in Drosophila melanogaster Through Sphingosine. Issue 3 (22nd May 2019) - Zhang, Chun-Hong; Zhang, Min-Jing; Shi, Xiao-Xiao; Mao, Cungui; Zhu, Zeng-Rong
Abstract: Alkaline ceramidase ( Dacer ) in Drosophila melanogaster was demonstrated to be resistant to paraquat-induced oxidative stress. However, the underlying mechanism for this resistance remained unclear. Here, we showed that sphingosine feeding triggered the accumulation of hydrogen peroxide (H2 O2 ). Dacer -deficient D. melanogaster ( Dacer mutant) has higher catalase (CAT) activity and CAT transcription level, leading to higher resistance to oxidative stress induced by paraquat. By performing a quantitative proteomic analysis, we identified 79 differentially expressed proteins in comparing Dacer mutant to wild type. Three oxidoreductases, including two cytochrome P450 ( CG3050, CG9438 ) and an oxoglutarate/iron-dependent dioxygenase ( CG17807 ), were most significantly upregulated in Dacer mutant. We presumed that altered antioxidative activity in Dacer mutant might be responsible for increased oxidative stress resistance. Our work provides a novel insight into the oxidative antistress response in D. melanogaster .